Diferentes metodologias para determinação dos coeficientes de metabolização dos nutrientes e energia de rações com duas espécies de papagaios do gênero Amazona - Menezes, Samara Dulce Temoteo (2018)
The objective of this study was to compare different methods of excreta collection in metabolic essays with two species of captive-bred parrots of the genos Amazona to determine the metabolization coefficients of dry matter, protein, gross energy and metabolizable energy of ration. Between the species, the objective was to determine the feed and energy intake per metabolic weight, consumption, waste and costs of experimental rations. For this purpose, 16 adult parrots were used, 4 pairs of turquoise-fronted parrots (Amazona aestiva) and 4 pairs of orange-winged parrots (Amazona amazonica), with 400g average weight, adapted to the captivity and distributed in a completely randomized design in a 2x2 factorial scheme (2 excreta collection methodologies x 2 species of parrots), totaling 4 treatments of 6 repetitions. Both species, orange-winged and turquoise-fronted parrots presented the same intake of ration, protein and energy per metabolic weight and the coefficients of metabolization of dry matter, protein and crude energy of the ration were also identical. The partial excreta collection from parrots of both species provided lower values of apparent metabolizable energy, corrected apparent metabolizable energy, coefficients of apparent metabolism of dry matter, crude protein and crude energy of rations when compared to those determined by the total excreta collection method. As for analyzes of ingestion and consumption, no significant difference was observed between the species of parrots, turquoise-fronted and orange-winged. Total excreta collection provides better results for energy values and feed metabolization coefficients for both species of parrots while the partial excreta collection using FDNi as an indicator underestimates it. The % MS diet formula - (% MS excreta * IF) underestimates the CMAMS when using partial excreta collection using the FDNi as indicator. Feed intake, nutrients and energy were identical between these parrots. The cost of food represented an average of BRL 1.11 / bird / day, being BRL 0.67 of this total spent on feed wastage.